2021
DOI: 10.3390/en14102749
|View full text |Cite
|
Sign up to set email alerts
|

How to Predict Energy Consumption in BRICS Countries?

Abstract: Brazil, Russia, China, India, and the Republic of South Africa (BRICS) represent developing economies facing different energy and economic development challenges. The current study aims to predict energy consumption in BRICS at aggregate and disaggregate levels using the annual time series data set from 1992 to 2019 and to compare results obtained from a set of models. The time-series data are from the British Petroleum (BP-2019) Statistical Review of World Energy. The forecasting methodology bases on a novel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 92 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…In contrast, energy consumption in Russia go behind the global trend of decreasing rate. (Khan & Osi nska, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, energy consumption in Russia go behind the global trend of decreasing rate. (Khan & Osi nska, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In 2018 energy output in China increased steadily, reaching 3.77 billion tons of coal equivalent, accounting for 18.7% of global production. Each year South Africa EX more than 45 Mtoe of coal to global markets as a net energy exporter; however domestic oil and natural gas production is lower and depends on the IM of most of these fuels (Khan & Osi nska, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Data used for the present study were the World Energy Balances for non-OECD nations between the years 1991-2015 published by the International Energy Agency (IEA), as well as the latest World Energy Balances for OECD nations as primary sources, and uses descriptive statistics to analyze the final energy consumption characteristics of the G7 and BRICS nations. Khan and Osińska (2021) attempted to forecast the consumption of energy in BRICS nations using the yearly time series data set from the years 1992-2019 from British Petroleum (BP-2019) Statistical Review of World Energy and to check the results obtained from a set of models like Fractional-order Grey Model, Autoregressive Integrated Moving Average (ARIMA) model, etc. The authors concluded that the BRICS countries should monitor energy production and consumption, focusing on the supply-demand gap of energy and its components and facilities provided to local and foreign investors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Coal accounts for 57% of the primary energy consumption in China, and ~ 85% of it is produced by underground mining (Wang et al, 2021b). In 2020, China's coal output was 3.902 billion tons, an increase of 1.20% from 2019, and the coal consumption was 4.30 billion tons, an increase of 0.30% over 2019, which accounted for 50.40% and 54.30% of global output and consumption, respectively (Khan & Osińska, 2021). The exploitation and utilization of coal seams have ensured economic benefits and energy security (Xiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%